Regular Exercise Decreases the Risk of Osteoporosis in Postmenopausal Women - Chu-Fen Chang; Jia-In Lee; Shu-Pin Huang; Shu-Pin Huang; Shu-Pin Huang; Shu-Pin Huang; Shu-Pin Huang; Jiun-Hung Geng; Jiun-Hung Geng; Jiun-Hung Geng; Jiun-Hung Geng; Jiun-Hung Geng; et al. (Frontiers Media S.A., 2022)
Regular exercise can regulate bone maintenance and improve bone health. However, large-scale epidemiological studies on the association between regular exercise and incident osteoporosis in menopausal women are still lacking. We aimed to examine the relationship between exercise and the risk of osteoporosis in menopausal women. In cross-sectional analysis, we enrolled 30,046 postmenopausal women with available information from the database of the Taiwan Biobank (TWB). We divided them into two groups according to their status of regular exercise, i.e., no exercise and regular exercise groups. A t-score of −2.5 or more standard deviations (SDs) below that of a young adult was defined as osteoporosis. Logistic regression after adjusting for confounding factors was used to analyze the association between regular exercise and the prevalence of osteoporosis. Furthermore, the risk of incident osteoporosis development was analyzed in a longitudinal cohort of 6,785 postmenopausal women without osteoporosis at baseline using a Kaplan-Meier analysis and a log-rank test. The mean age of subjects in the cross-sectional cohort was 59 years old. Fifty-six percent of them were exercising regularly. Osteoporosis was observed in 1,886 (14.2%) and 2,254 (13.4%) participants in the no exercise and regular exercise groups. Lower risk of osteoporosis was noted in postmenopausal women with regular exercise when compared with those without regular exercise [odds ratio (OR), 0.76; 95% confidence interval (95% CI), 0.71-0.81]. In the longitudinal cohort, incident osteoporosis was found in 430 (10.5%) women with regular exercise and 299 (11.2%) women without exercise during a mean follow-up of 45 months. Cox regression analysis revealed that the risk for incident osteoporosis was lower in postmenopausal women with regular exercise than those without exercise [hazard ratio (HR), 0.83; 95% CI, 0.71-0.97]. Our study suggests that regular exercise is associated with a reduced risk of osteoporosis in postmenopausal women and strengthens the importance of exercise for the prevention of osteoporosis.